The influence of place attachment on community leadership and place management. Issue 3 (2nd August 2021) - Grocke, Craig Lance; Eversole, Robyn; Hawkins, Clayton Jon
Abstract : Purpose: This paper aims to draw on Seamon's(2012a, 2012b, 2014, 2015, 2018 ) theories on the "processes of place attachment" to understand the influence of place attachment on community leadership and the management of four towns in the Barossa region of South Australia. Design/methodology/approach: The research methodology combines photo-elicitation, participant observation and in-depth interviews with 12 community leaders across four town groups. Scannell and Gifford's(2010) tripartite model for place attachment is used to segment qualitative interview data to understand the nature of place attachment of community leaders. This was followed by thematic analysis using Seamon's(2012a, 2014, 2018 ) six processes of place attachment to understand how the dynamics of place attachment as a series of processes interact to influence community leadership and place-based action. Findings: The research revealed that community leaders in the Barossa region regularly confront a tension between the "Being" and "Becoming" of Place. It also suggests that place attachment for new residents is accelerated by engaging multiple place attachment processes; these can be measured using the research methodology in this study. The result is a tipping point where place leadership from new residents can accelerate towards the "Being of Place" showing a tendency towards protectionist behaviour commonly seen amongst long-term residents. Research limitations/implications: Testing the findings in this paper in other rural regions and other cultural contexts will add further insight and validation of these findings. It is recommended that future research could further develop this approach through engaging multiple place-based community groups in the same town and across different locations to understand the pattern language of communities with more accuracy. Practical implications: This study has enabled a deeper understanding of place-based community groups and their motivations to protect the status quo or promote change in the development and management of the place. Each community requires a tailored approach to place management and development to activate community resources and partnerships successfully. This research also provides knowledge on how to accelerate place attachment for new residents to improve their sense of belonging, value and purpose by engaging programs that engage all six place attachment processes. Social implications: The research reveals that place relations are dynamic, complex and often political. Rural towns display a pattern language for how they engage networks and resources that government needs to understand to engage community stewardship of place – its social, environmental and economic setting. This research offers a method to better understand the pattern language of place attachment that drives community leadership and place management to help communities sustain themselves and adapt to change. Originality/value: The research explores the inter-relationship between the place attachment of community leaders and their response to change from different types of community impacts such as bushfires or the COVID-19 pandemic. Understanding these processes is valuable in informing place management partnerships between community, business and government.